Enhancing aesthetic appreciation by priming canvases with actions that match the artist's painting style - Ticini, Luca F.; Rachman, Laura; Pelletier, Jerome; Dubal, Stephanie (Frontiers in Human Neuroscience, 2014)
The creation of an artwork requires motor activity. To what extent is art appreciation divorced from that activity and to what extent is it linked to it? That is the question which we set out to answer. We presented participants with pointillist-style paintings featuring discernible brushstrokes and asked them to rate their liking of each canvas when it was preceded by images priming a motor act either compatible or incompatible with the simulation of the artist’s movements. We show that action priming, when congruent with the artist’s painting style, enhanced aesthetic preference. These results support the hypothesis that involuntary covert painting simulation contributes to aesthetic appreciation during passive observation of artwork.